Sudan : Request for a 39-Month Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Sudan. (IMF Staff Country Reports; Country Report, 2021)
Since the 2019 popular revolution, Sudan's transitional government has taken difficult steps to right decades of economic mismanagement. The challenges facing the authorities remain significant, but they have fulfilled the necessary conditions to reach the HIPC Decision Point (DP). This is an historic achievement and Sudan is set to clear its arrears and normalize relations with the IMF and other international financial institutions. This will unlock Sudan's access to new financial resources to fund much needed development and social spending.